Currency Mismatches and Corporate Default Risk : Modeling, Measurement, and Surveillance Applications - Santos, Andre; Chan-Lau, Jorge (Washington, D.C. : International Monetary Fund, 2006)
Currency mismatches in corporate balance sheets have been singled out as an important factor underlying the severity of recent financial crises. We propose several structural models for measuring default risk for firms with currency mismatches in their asset/liability structure. The proposed models can be adapted to different exchange rate regimes, are analytically tractable, and can be estimated using available equity price and balance sheet data. The paper provides a detailed explanation on how to calibrate the models and discusses two applications to financial surveillance: the measurement of systematic risk in the corporate sector and the estimation of prudential leverage ratios consistent with regulatory capital ratios in the banking sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet